Perubahan Bunyi Kata Serapan Keagamaan dari Bahasa Arab ke dalam Bahasa Jawa - Muhammad Sayyidul Arwan (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Word absorption is one of source language borrowing process taken by absorbing languages. In this process, there will be sound changes in the absorption word. This study will discuss the form of sound changes of word absorption in a religious study from Arabic language to Javanese language using equal method of Crowley’s theory. This research aims to figure out the form of sound changes of word absorption in Javanese language. As for the results of this research showing the forms of sound changes in word absorption from Arabic language to Javanese language using sound change theory of Crowley are as below: a) lenition consists of cluster reduction, apocope, sincope, and compression, b) sound addition including of anaptyxis and epenthesis, c) metathesis, d) assimilation, e) disimilasi. While the unfigured out sound changes consist of haplology, fusion, prothesis, unpacking, vowel breaking, and abnormal sound changer. In this research, the researcher finds the other unrevealed symptoms of Crowley’s sound changes theory as below: apheresis, sound lax, strengthening sound, paragogue, monoftongization, and abbreviation.